INDEKS KEPUASAN MASYARAKAT (IKM) UNTUK KUALITAS PELAYANAN PUBLIK DI KECAMATAN PELAWAN KABUPATEN SAROLANGUN - Sulastri Sulastri (Jurnal Dinamika Manajemen, 2015)
This study aims to determine the quality of services provided by the Pelawan District Office to the community and to determine the level of community satisfaction for the services provided by the Pelawan District Office. The qualitative descriptive research design is a mixed qualitative and quantitative one to determine the community satisfaction index from services in Pelawan District, Sarolangun Regency. The results of the study concluded that there are still many dimensions and indicators of customer satisfaction in the unfavorable category so that it can be said that service quality in Pelawan District is also in the unfavorable category, there are 2 dimensions whose categories are not good, namely fairness in getting service and certainty of service costs. Overall, the performance value of IKM service units is categorized as unfavorable.